USING TEXT-RELATED PICTURE TO INCREASE STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT - Diah Paramita Sari (INOVISH JOURNAL, 2017)
Abstract: Reading as one of the language skills needs to be developed at various levels of education so that students are able to understand the contents of the reading well, especially texts that use the English language. This study aims to discuss one way to solve students’ problem in reading descriptive text which is by using text-related picture. The text used is descriptive text. In this activity, the teacher shows the picture that is related to the text that will be given. The teacher asks the students about the pictures and brainstorms their knowledge about the picture. Therefore, it is expected to the English teachers to be able to develop the students' reading skill by using the right strategy so that the students can understand the English reading texts quickly and easily. Through this image media teachers can guide students to the text to be learned. Finally the authors hope this paper can be useful for English teachers as an alternative strategy applied in teaching reading.